A busca de sentido e os buscadores de Deus no Evangelho de Lucas: um desafio aos cristão de classe média - Teixeira, Paulo Couto (2011)
This is a study about the search for God and finding meaning in existence, with emphasis on seekers who went to Jesus, stimulated by an imperative of its core, as narrated in the Gospel of Luke. The goal is to identify motivations, results and demands for personal conversion, tracking and following of Jesus, that can guide the pastoral groups linked to the traditional middle classes. The first chapter treats with the restlessness of the human soul - the reasons for the demand of basic needs to the search for meaning, considering philosophical thoughts and self- transcendence. The second chapter is devoted to the Search for God: the encounter as a gift, and the perspective of God as the Unconditioned (Tillich), presents God as a seeker by human being (Heschel) and ends by analyzing the search for God in other spiritual dimensions. The third chapter considers Jesus of Nazareth as a seeker of God, starting from the Palestinian context and the choices made by Jesus in his ministry. In the fourth chapter - seekers and Jesus - are shown the criteria for choosing the Gospel (Luke) and selection of pericopes: the Bethany sinner (Luke 7, 36-49), the rich man (Lk. 18.18-29); Zacchaeus (Luke 19.1-10), and Joseph of Arimathea (Luke 24.50-55). the analysis was finished with one study the Magi (Matthew 2.1- 12) and owned from Gerasa (Luke 8.26-39). The fifth chapter articulates self-transcendence and follow Jesus. Among the findings highlight that the conversion and metanoia comes accompanied by the distribution of wealth and stripping in favor of the poor. It was also noted that the search for God is always related to the search for meaning. The pivot point is the mercy for the poor and the discovery of God as "Unconditioned." It also concludes that the follow-up, discipleship, conversion and self-transcendence are related, and that follow-up and discipleship are manifested through successive levels and times. Another conclusion is that Jesus also lived his self-transcendence, as a seeker of God, and interfaith dialogue and ecumenism can be facilitated by the special relevance of mercy to the poor as the imperative of metanoia.